On the Mechanism of Re(I)–Carboxylate Bond Cleavage by Perchloric Acid: A Kinetic and Spectroscopic Study - Fagioli, Ulises (2011)
We have studied the reaction between pz-CO2-Re(CO)3(bpy) and perchloric acid in acetonitrile by following the UV-vis and IR spectral changes in the reaction mixture. A fast equilibrium was found to be established between solvated protons, pz-CO2-Re(CO)3(bpy) and the protonated intermediate [pz-C(OH)O-Re(CO)3(bpy)]+ which finally yields pz-COOH and Re(CO)3(bpy)(CH3CN)+ as reaction products. This intermediate has been characterized by UV-vis and IR spectroscopies and by DFT calculations. The fully optimized DFT/CPCM structures for pz-CO2-Re(CO)3(bpy) and [pz-C(OH)O-Re(CO)3(bpy)]+ were compared with the X-ray structure of pz-CO2- Re(CO)3(bpy). The structural parameters associated to the carboxyl group in the protonated intermediate are between those of pz-CO2-Re(CO)3(bpy) and pz-COOH. Multivariate curve resolution methods were employed to obtain the spectrum of the protonated intermediate and the concentration profiles from the full matrix of timeresolved UV-vis spectra. The proposed mechanism was numerically simulated by using Runge-Kutta methods. Model parameters were estimated by non-linear regression fitting of the concentration profiles, yielding values of log(K) = 4.9 ± 0.3 and k = 0.16 ± 0.03 min-1 for the formation equilibrium constant and the decay rate constant of the protonated intermediate, respectively.